Makna Mengampuni dalam Matius 18:21–22: Kajian Biblika dan Implikasinya bagi Umat Kristen Masa Kini - Alvin Budiman Kristian; Resa Junias (Sekolah Tinggi Alkitab Jember, 2026)
Forgiveness is a central teaching of Christianity, but its practice often faces challenges due to interpersonal conflict, retaliation, and the phenomenon of cancel culture. Therefore, an examination of Matthew 18:21–22 is crucial for understanding the meaning of forgiveness in Jesus' teachings and its relevance for the church today. This research uses qualitative methods with a biblical approach through historical-contextual and linguistic analysis of the text of Matthew 18:21–22. The results show that forgiveness is not merely a moral requirement, but a relational principle aimed at restoring community and building reconciliation. The phrase